2013
DOI: 10.1177/0333102413505241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posterior hypothalamus region deep brain stimulation on sleep

Abstract: PH-DBS, a promising treatment for severe refractory TACs, affects sleep quality and pre-existing sleep disorders. This needs to be considered when treating patients with PH-DBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Interestingly, the polysomnogram of cluster headache patients (both inside or outside a cluster period) may show decreased number and frequency of REM sleep periods ( Sahota and Dexter, 1990 ; Barloese et al, 2015 ), though REM sleep abnormalities are not always reported ( Vetrugno et al, 2007 ). The alleviation of cluster headache symptoms after posterior hypothalamic DBS implantation may also be accompanied by changes in sleep quality and architecture, though these changes are not always pleasant (e.g., frequent overnight awakenings) ( Vetrugno et al, 2007 ; Kovac et al, 2014 ).…”
Section: Circadian Rhythm/sleepmentioning
confidence: 99%
“…Interestingly, the polysomnogram of cluster headache patients (both inside or outside a cluster period) may show decreased number and frequency of REM sleep periods ( Sahota and Dexter, 1990 ; Barloese et al, 2015 ), though REM sleep abnormalities are not always reported ( Vetrugno et al, 2007 ). The alleviation of cluster headache symptoms after posterior hypothalamic DBS implantation may also be accompanied by changes in sleep quality and architecture, though these changes are not always pleasant (e.g., frequent overnight awakenings) ( Vetrugno et al, 2007 ; Kovac et al, 2014 ).…”
Section: Circadian Rhythm/sleepmentioning
confidence: 99%
“…30 These data are complementary to data from recent human trials of posterior hypothalamic stimulation for the treatment of cluster headaches that report prolonged periods of wakefulness and disrupted sleep after DBS. 48…”
Section: Hypothalamusmentioning
confidence: 99%
“…Much of what is known about neurostimulation and sleep derives from the use of DBS to treat movement disorders like Parkinson's disease . DBS of some brainstem structures, including the subthalamic nucleus and the pedunculopontine nucleus, is generally associated with improvement in sleep quality, but development of a sleep disorder is possible too, and stimulation of other deep targets can worsen sleep . The therapeutic mechanisms of VNS and DBS are thought to involve brainstem pathways that also play important roles in sleep, but RNS System leads are typically placed in the neocortex or hippocampus, where the effects of stimulation on sleep are less clear.…”
Section: Discussionmentioning
confidence: 99%